(untitled) (International relations and international law Journal, 2016)
In the article the policy of tsarist government associated with the Azerbaijan lands containing oil in the XIX century is investigated. İn 1806 Baku khanete having been occupied by Russia the rich oil wells belonging to the people were confiscated and were included into the treasury of the tsarist government. İn 1808 the oil- containing lands were given by affidavit. The Affidavit system existed till 1872 by intervals. İn 1872 as to the law of the system of giving lands by affidavit was liquidated and the oil wells were privatized by the way of auction.The peasants living on the oil- containing land were entitled with the right to rent the land for the period of from 12 till 30 years. But payment was very hard. The tsarist government under the pretext that those lands were not favorable lands for plaughing and by other pretexts took away the lands from the hands of the peasants.